Reawakening the Developmental Origins of Cancer Through Transposable Elements - Lynch-Sutherland, Chiemi F.; Chatterjee, Aniruddha; Stockwell, Peter A.; Eccles, Michael R.; Macaulay, Erin C. (Frontiers in Oncology, 2020)
Transposable elements (TEs) have an established role as important regulators of early human development, functioning as tissue-specific genes and regulatory elements. Functional TEs are highly active during early development, and interact with important developmental genes, some of which also function as oncogenes. Dedifferentiation is a hallmark of cancer, and is characterized by genetic and epigenetic changes that enable proliferation, self-renewal and a metabolism reminiscent of embryonic stem cells. There is also compelling evidence suggesting that the path to dedifferentiation in cancer can contribute to invasion and metastasis. TEs are frequently expressed in cancer, and recent work has identified a newly proposed mechanism involving extensive recruitment of TE-derived promoters to drive expression of oncogenes and subsequently promote oncogenesis—a process termed onco-exaptation. However, the mechanism by which this phenomenon occurs, and the extent to which it contributes to oncogenesis remains unknown. Initial hypotheses have proposed that onco-exaptation events are cancer-specific and arise randomly due to the dysregulated and hypomethylated state of cancer cells and abundance of TEs across the genome. However, we suspect that exaptation-like events may not just arise due to chance activation of novel regulatory relationships as proposed previously, but as a result of the reestablishment of early developmental regulatory relationships. Dedifferentiation in cancer is well-documented, along with expression of TEs. The known interactions between TEs and pluripotency factors such as NANOG and OCTt4 during early development, along with the expression of some placental-specific TE-derived transcripts in cancer support a possible link between TEs and dedifferentiation of tumor cells. Thus, we hypothesize that onco-exaptation events can be associated with the epigenetic reawakening of early developmental TEs to regulate expression of oncogenes and promote oncogenesis. We also suspect that activation of these early developmental regulatory TEs may promote dedifferentiation, although at this stage it is hard to predict whether TE activation is one of the initial drivers of dedifferentiation. We expect that developmental TE activation occurs as a result of the establishment of an epigenetic landscape in cancer that resembles that of early development and that developmental TE activation may also enable cancers to exploit early developmental pathways, repurposing them to promote malignancy.